Results From the First Teleglaucoma Pilot Project in Addis Ababa, Ethiopia. Issue 8 (August 2019) - Giorgis, Abeba T.; Alemu, Abiye M.; Arora, Sourabh; Gessesse, Girum W.; Melka, Fikru; Woldeyes, Alemayehu; Amin, Samreen; Kassam, Faazil; Kurji, Ayaz K.; Damji, Karim F.
Abstract : Precis: A teleglaucoma case-finding model was utilized in Ethiopia using a high-risk case identification approach. An overall 7.9% of patients had definite glaucoma, and 13.8% were glaucoma suspects. Most cases could be managed medically. Background: This study was carried out to analyze disease prevalence and clinical referral pathways for high-risk patients assessed through a hospital-based teleglaucoma case-finding program. Methods: Patients over the age of 35 years were referred from outpatient diabetic and hypertensive clinics. Through a teleglaucoma consultation, a glaucoma specialist provided remote diagnosis and management recommendations. Patient referral pathways were analyzed. Part way through the program, frontline ophthalmic nurses and optometrists were empowered to refer patients to be seen by general ophthalmologists within a week if patients met high-risk criteria. Qualitative stakeholder feedback was also obtained. Results: A total of 1002 patients (53% female) were assessed with a mean age of 51.0±11.7 years. The prevalence of glaucoma and glaucoma suspects was 7.9% (79 cases) and 13.8% (138 cases), respectively. Retinopathy was found in 9.1%, with hypertensive retinopathy (2.7%) and diabetic retinopathy (2.5%) representing the majority of cases. Age-related macular degeneration was present in 1.5% and cataract in 16%. An overall 63% of cases were without organic eye disease. 35% of patients were referred to a general ophthalmologist, 0.7% to a glaucoma specialist (for surgery), 1.5% to a retina specialist, and 17.7% to an optometrist for further care. Qualitative analysis revealed that stakeholders felt the value of teleglaucoma would be in triaging patients requiring more urgent management and in identifying disease at an earlier stage. Conclusions: There is a high prevalence of glaucoma in Ethiopian patients assessed through this teleglaucoma program. This model and study have also demonstrated various principles behind telemedicine, such as the development of an intelligent triage system, case-finding for a variety of diseases, and consideration of optimal patient flow/referral pathways. Abstract : Supplemental Digital Content is available in the text.